Seasonal Variation in Helminth Parasites of Snakeheads Channa Punctatus and Channa Striatus (Perciformes: Channidae) in Uttar Pradesh, India - Gautam, N. Kumari (Helminthologia, 2018)
Snakehead fishes are widely consumed throughout South East Asia, China and India because of their good taste of meat and high nutrient values such as presence of prostaglandins, thromboxane and Omega-6 fatty acid. Parasitic infection constitutes significant economic loss in fish production. The aim of this work was to study the seasonal variation of helminths in snakeheads. In the presented study, a three-year survey has been performed. A total of 1013 individuals of Channa punctatus and 247 individuals of Channa striatus were examined. A total of 3783 helminths were collected, with an average of 3.02 helminths/fish. 43.50 % individuals of C. punctatus and 59.10 % of C. striatus were found to be infected with acanthocephalans, trematodes, nematodes and cestodes per year. The prevalence and mean abundance of Pallisentis sp. was at its peak in summer. However the prevalence of trematodes, nematodes and cestodes was at peak during autumn. Mean abundance of nematodes was at peak in summer. Interestingly, the males were found more infected as compared to the females and the infection rate in males peaked in summer. In comparison to other weight groups, medium size hosts (21 – 40 g) were found more consistently infected. Thus the results indicate that there are seasonal variations in parasitic helminths infecting C. punctatus and C. striatus which also depend upon sex and weight. These variations may be attributed to various environmental and biological factors including parasite life cycle and immune level of host.